A Seismic Monitoring Tool for Tidal-Forced Aquifer Level Changes in the Río de la Plata Coastal Plain, Argentina - Galone, Luciano (2024)
Ambient seismic noise has gained extensive applications in seismology and plays a pivotalrole in environmental seismic studies. This study focuses on the Río de la Plata Coastal Plain, employingthe horizontal-to-vertical spectral ratio (HVSR) method on ambient seismic noise recordsto analyze subsurface dynamics. The region’s hydrogeology is complex, featuring partially interconnectedcoastal aquifers. The HVSR analysis reveals two peaks, with P0 associated with thesediment-basement interface and P1 linked to a shallower stratigraphic discontinuity. Temporalanalysis of P1 highlights cyclical patterns correlated with estuarine levels, suggesting a relationshipbetween variations in seismic velocities and tidal dynamics. Comparisons with aquifer data supportthe hypothesis that tidal variations influence subsurface mechanical properties, impacting the HVSRfunction. The study hints at the potential of ambient seismic noise analysis as a non-invasive and costeffectivemethod for studying coastal aquifers and understanding groundwater dynamics. Ongoingresearch aims to further explore these relationships for enhanced groundwater resource management.